1989
DOI: 10.1002/cjce.5450670310
|View full text |Cite
|
Sign up to set email alerts
|

The reaction network for the oxidation of propylene over a bismuth molybdate catalyst

Abstract: An initial-rate study was conducted to determine the kinetics of the oxidation of acrolein over a bismuth molybdate catalyst. The results were combined with results from a previous initial-rate study of propylene oxidation on the same catalyst to develop a quantitative description of the reaction network for propylene oxidation.The redox steady-state model with half-order in oxygen which provided the best fit to the propylene oxidation data also provided the best fit to the acrolein oxidation data. The disappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…The formation of acetaldehyde seems to take place in a parallel reaction from propylene ( r 5 ) by C–C bond scission, as can be concluded from the nonzero initial slope of the yield–time curve. This is also in good agreement to a variety of experimental data reported elsewhere. ,,,,, Since the selectivity to acetaldehyde increased or stayed almost constant with an increasing conversion of propylene, it is concluded that acetaldehyde is also produced by an additional consecutive reaction. In this regard, it can be assumed that a further oxidation step of acrolein ( r 6 ) results in acetaldehyde. ,, In both reactions, oxidation of propylene and oxidation of acrolein, the C–C bond scission to form acetaldehyde leads to carbon oxides as additional byproducts.…”
Section: Modelingsupporting
confidence: 92%
See 3 more Smart Citations
“…The formation of acetaldehyde seems to take place in a parallel reaction from propylene ( r 5 ) by C–C bond scission, as can be concluded from the nonzero initial slope of the yield–time curve. This is also in good agreement to a variety of experimental data reported elsewhere. ,,,,, Since the selectivity to acetaldehyde increased or stayed almost constant with an increasing conversion of propylene, it is concluded that acetaldehyde is also produced by an additional consecutive reaction. In this regard, it can be assumed that a further oxidation step of acrolein ( r 6 ) results in acetaldehyde. ,, In both reactions, oxidation of propylene and oxidation of acrolein, the C–C bond scission to form acetaldehyde leads to carbon oxides as additional byproducts.…”
Section: Modelingsupporting
confidence: 92%
“…This behavior indicates that acetaldehyde is formed by a parallel reaction from propylene which is in very good agreement to studies reported in literature. [2][3][4]7,8,35,36,47 The strong increase of the formation at conversion levels higher than 80% further provides evidence for a consecutive reaction. The results from the variation of the feed composition (molar ratios) further substantiate the conclusion that acetaldehyde is formed in a parallel as well as consecutive reaction.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…14,20 Beside the target product acrolein, various by-products originating from parallel and/or consecutive reactions are known. Thus, complex reaction networks [20][21][22][23][24][25][26][27] have been proposed to elucidate the origin of by-products including carbon monoxide, carbon dioxide, acrylic acid, acetic acid, acetaldehyde, formaldehyde, and others. From an industrial point of view, knowledge of reaction networks is essential to understand the processes taking place inside the reactor.…”
Section: Introductionmentioning
confidence: 99%